Analysis of Secondary Diagnosis of COVID-19 in Children Aged 0-18: A Case Study of an Inpatient at Hospital X in Central Java Province - B Betti, Florensia; Amalia, Afia; Asya Salwa Munna, Niantiara; Widianawati, Evina (International Journal of Health Literacy and Science, 2023)
Children ages 0 - 18 are more susceptible to infected COVID-19. The prognosis of pediatric patients can be significantly worse by the presence of a secondary diagnosis. This study's aim was to categorize pediatric patients according to their age, sex, length of stay (LOS), subsequent diagnoses, and treatments. Samples were taken from the medical records of 19 pediatric patients, ages 0-18, who were hospitalized at X Hospital. The data are descriptively analyzed in this study using secondary data taken from the medical records of pediatric patients from April 2020 to February 2021. According to the study's findings, 79% of the pediatric COVID-19 patients were under the age of five, 58% of them were men, and their average length of stay was 9.53 days. The most common secondary diagnoses were Febrile convulsions (9%) and Hypo-osmolality and hyponatraemia (9%). Microscopic inspection of specimen from the ear, nose, throat, and larynx (35%), Other chest x-ray (27%), and Microscopic examination of blood (8%) were the treatment and procedures that were performed the most frequently. Children who are COVID-19 patients between the ages of 0 - 18 have a high number of secondary diagnoses and medical procedures during therapy, necessitating more intensive monitoring.